Relationship of Innovativeness with Social Justice: an Example from Fishermen Community in Pulau Harapan, Indonesia - Mohammad Balya Ali Syaban (Universitas Muhammadiyah Sidoarjo, 2019)
This research aims to determine the relationship between the innovativeness of fishermen on the Islands with social Expectations North thousand islands. The method used was a survey with the study involving 75 sample correlations. There are two instruments in measurement to the study of social justice (reliability = .923), and innovativeness (reliability = .952). This research data were analyzed using regression correlation which is then verified by test-t and F-test. The results of this research show that there is a positive and significant correlation between innovativeness with social justice. It can therefore be inferred if the fisherman's increased social justice then innovativeness will be a consideration.